COVID-19's effects on future pro-environmental traveler behavior: an empirical examination using norm activation, economic sacrifices, and risk perception theories. Issue 1 (9th December 2021) - O'Connor, Peter; Assaker, Guy
Abstract: This study examines how the COVID-19 pandemic will influence people's pro-environmental travel behavior (PETB) and potentially prompt more ecological/sustainable future travel. A comprehensive model using the norm-activation model (NAM), economic sacrifices theory, and the perceived risks associated with COVID-19 is presented and tested using structural equation modeling on data collected from US travelers during April 2020. The results revealed the adequacy of the proposed model and the above-mentioned theories/constructs in explaining post-COVID-19 PETB (R 2 = 72.1%). Risk perception of COVID-19 was found to influence PETB indirectly through the NAM constructs of environmental concerns (EC), environmental responsibility (ER), environmental moral obligation (EMO) and willingness to make economic sacrifices for environmental protection. These results illuminate the mechanism through which COVID-19 is likely to influence future pro-environmental travel behavior as well as provide important managerial implications for tourism.